Співвідношення трудового та цивільно-правового договору: проблеми відмежування - Князькова, Л. М.; Knіazkova, L. M. (Маріупольський державний університет, 2024)
У статті проводиться аналіз співвідношення трудового договору та цивільноправових договорів, пов’язаних з працею. Досліджено загальні риси між трудовим та цивільно-правовими договорами. Автором проаналізовано судову практику щодо застосування трудових та цивільно-правових договорів при реалізації громадянами України права на працю у сучасних умовах. Проаналізовано трудовий договір з нефіксованим робочим часом як особливий вид трудового договору, умовами якого не встановлено конкретний час виконання роботи, а обов’язок працівника виконувати роботу, яка виникає виключно в разі її надання роботодавцем, без гарантування того, що така робота буде надаватися постійно, але з дотриманням умов оплати праці, що передбачені КЗпП. Акцентовано увагу на особливостях трудового договору про дистанційну роботу, який введено у трудове законодавство з початком пандемії, а потім – з воєнним станом. Висвітлено спрощений режим регулювання трудових відносин у сфері малого і середнього підприємництва в умовах воєнного стану, який дає можливість сторонам договору враховувати додаткові права та обов’язки, що зближує цей вид договору з цивільно-правовим, але при цьому пільги та гарантії, передбачені трудовим законодавством, за працівником зберігаються. Досліджено особливості праці домашніх працівників, у трудовому договорі яких сторони самостійно домовляються про ведення облікової документації, додаткових підстав звільнення за ініціативою роботодавця, добровільності працівника брати участь у соціальному страхуванні та ін. Автором зроблено висновок про те, що трудовий договір у сучасних умовах зберігає свою соціальну природу і не може бути замінений цивільно-правовими договорами про працю. При цьому використання гнучких форм праці виключає деякі традиційні ознаки трудового договору, зберігаючи при цьому усі соціальні гарантії для працівників.

The article analyses the correlation between the employment contract and civil law contracts related to work. Common features between labour and civil law contracts have been studied. It was noted that the International Labour Organization determines that the main criteria for distinguishing labour relations from similar other relations related to work are "subordination" and dependence." The author compared the common features of the employment contract and the civil law contract as the forms of realization of the right for work, revealed the fundamental differences between labour and civil law contracts related to work, analysed the judicial practice regarding the application of labour and civil law contracts in the implementation of the right for work by citizens of Ukraine in present conditions. Taking into account the legislation and judicial practice, the correlation between the employment contract and civil law contracts related to work was determined, taking into account the introduction of flexible forms of work into the labour legislation of Ukraine. An employment contract with non-fixed working hours is analysed as a special type of employment contract, the terms of which do not establish a specific time of work performance, the obligation of the employee to perform work that arises only in the case of its provision by the employer, without guaranteeing that such work will be provided constantly, but in compliance with the conditions of payment of labour stipulated by the Labour Code. Attention is focused on the peculiarities of the labour contract on remote work, which was introduced into the labour legislation with the beginning of the pandemic, and then with martial law. The simplified regime for the regulation of labour relations in the field of small and medium-sized enterprises under martial law is highlighted, which allows the parties to the contract to take into account additional rights and obligations, which brings this type of contract closer to the civil law, but at the same time benefits and guarantees provided for by labour legislation for an employee are preserved. The peculiarities of the work of domestic workers, in whose employment contract the parties independently agree on keeping accounting documentation, additional grounds for dismissal at the initiative of the employer, the employee's voluntary participation in social insurance, etc., were studied. The author concluded that the employment contract in modern conditions retains its social nature and cannot be replaced by civil law labour contracts. At the same time, the use of flexible forms of work excludes some traditional features of the employment contract while preserving all social guarantees for employees. Since judicial practice shows that when using different forms of work, difficulties arise in distinguishing labour relations from civil law, the author emphasized the priority determination in favour of labour relations and proposed to include this provision in the labour legislation of Ukraine.
Some issues of the correlation of employment and civil law contract
Keywords: трудовий договір; цивільно-правові договори; пов’язані з працею; дистанційна робота; трудовий договір з нефіксованим робочим часом; employment contract; civil law contracts related with remote work; employment contract with non-fixed working hours; remote work